Single-pulse ultrafast real-time simultaneous planar imaging of femtosecond laser-nanoparticle dynamics in flames - Mishra, Yogeshwar Nath; Wang, Peng; Bauer, Florian; Gudipati, Murthy S.; Wang, Lihong V. (Light: Science & Applications, 2024)
The creation of carbonaceous nanoparticles and their dynamics in hydrocarbon flames are still debated in environmental, combustion, and material sciences. In this study, we introduce single-pulse femtosecond laser sheet-compressed ultrafast photography (fsLS-CUP), an ultrafast imaging technique specifically designed to shed light on and capture ultrafast dynamics stemming from interactions between femtosecond lasers and nanoparticles in flames in a single-shot. fsLS-CUP enables the first-time real-time billion frames-per-second (Gfps) simultaneous two-dimensional (2D) imaging of laser-induced fluorescence (LIF) and laser-induced heating (LIH) that are originated from polycyclic aromatic hydrocarbons (PAHs) and soot particles, respectively. Furthermore, fsLS-CUP provides the real-time spatiotemporal map of femtosecond laser-soot interaction as elastic light scattering (ELS) at an astonishing 250 Gfps. In contrast to existing single-shot ultrafast imaging approaches, which are limited to millions of frames per second only and require multiple laser pulses, our method employs only a single pulse and captures the entire dynamics of laser-induced signals at hundreds of Gfps. Using a single pulse does not change the optical properties of nanoparticles for a following pulse, thus allowing reliable spatiotemporal mapping. Moreover, we found that particle inception and growth are derived from precursors. In essence, as an imaging modality, fsLS-CUP offers ultrafast 2D diagnostics, contributing to the fundamental understanding of nanoparticle’s inception and broader applications across different fields, such as material science and biomedical engineering.
CRIS-Team Scopus Importer:2024-09-13